FEM ANALYSIS OF THE INFLUENCE OF THE PLATE GEOMETRY ON THE BUCKLING DELAMINATION OF A PIEZOELECTRIC SANDWICH RECTANGULAR THICK PLATE - Aylikci, Fatih; Yahnioglu, Nazmiye; Elibol, Armagan (YILDIZ TECHNICAL UNIV, 2018)
In this study, we attempt to investigate the influence of the plate geometry on a buckling delamination of a PZT/Metal/PZT sandwich rectangular thick plate with lengths l(1) and l(3), and with thickness h. We assume that between the face and core layers there are two parallel interface-band cracks. We also assume that the considered thick plate is mechanically simply supported and unelectroded with vanishing normal electric displacement on its four lateral edges and, ideal contact conditions are satisfied between the interfaces of the contact layers. This plate is compressed only two lateral surfaces by the uniform uniaxial normal forces and there are neither mechanically nor electrically forces act on the upper and lower surfaces and also cracks' surfaces of the rectangular sandwich plate. The considered boundary value problems is modeled mathematically within the scope of the exact geometrically nonlinear equations of the theory of electro-elasticity within the scope of the piecewise homogeneous body model and is solved numerically by using 3D-FEM. The influence of various material and geometric parameters as well as the couple effect between the electrical and the mechanical fields on the buckling delamination of the rectangular thick plate is analyzed and discussed.
Keywords: Piezoelectric sandwich rectangular thick plate; buckling-delamination; FEM; Engineering